Релятивіська дзиґа в динаміці Остроградського - Мацюк, Р. (Праці наукового товариства ім. Шевченка, 2011)
A variational equation of the fourth order for the free relativistic top is developed starting from the Dixon's system of equations for the motion of the relativistic dipole. The obtained equation is then cast into the homogeneous space time Hamiltonian form.